Female Labour Supply, Human Capital and Welfare Reform - Richard Blundell W.; Monica Costa Dias; Costas Meghir; Jonathan Shaw (Institute for the Study of Labor (IZA), 2013)
We consider the impact of tax credits and income support programs on female education choice, employment, hours and human capital accumulation over the life-cycle. We analyze both the short run incentive effects and the longer run implications of such programs. By allowing for risk aversion and savings, we quantify the insurance value of alternative programs. We find important incentive effects on education choice and labor supply, with single mothers having the most elastic labor supply. Returns to labor market experience are found to be substantial but only for full-time employment, and especially for women with more than basic formal education. For those with lower education the welfare programs are shown to have substantial insurance value. Based on the model, marginal increases to tax credits are preferred to equally costly increases in income support and to tax cuts, except by those in the highest education group.
Keywords: J22; J24; H31; 330; labour supply; human capital; welfare reform